Transformation of Jamu Turmeric Asem Marketing Strategy from Traditional to Semi-Digital Approach in Sharia Economic Perspective: A Case Study of Oemah Turmeric Asem Kaligangsa - Faiq Rafi'ulhaq (Ecopreneur : Jurnal Ekonomi dan Bisnis Islam, 2026)
Marketing transformation is an important need for micro, small, and medium enterprises (MSMEs), including traditional herbal medicine businesses, in dealing with changes in consumer behavior and the development of digital technology. This study aims to analyze the transformation of the marketing strategy of Asem Turmeric Herbal Products from traditional marketing to a semi-digital approach in Oemah Turmeric Asem Kaligangsa. This study uses a qualitative approach with a case study method. Data collection was carried out through in-depth interviews, field observations, and documentation during the period from July to October 2025. The data analysis used the interactive model of Miles, Huberman, and Saldaña which included data reduction, data presentation, and conclusion drawn, and was tested for validity through triangulation of sources and techniques.The results show that before the transformation, marketing strategies were still dominated by direct sales and word-of-mouth promotion with limited market reach. The transformation to semi-digital marketing is done gradually through the use of simple digital media such as instant messaging apps and social media, without abandoning traditional marketing. The implementation of this strategy opens up opportunities for market expansion, increased product visibility, and attracted younger consumers. However, marketing transformation also faces challenges in the form of limited digital literacy, human resources, and promotion consistency. This study concludes that semi-digital marketing is an effective adaptive and contextual strategy in supporting the sustainability of traditional herbal medicine businesses without having to fully digitize.Viewed from the perspective of sharia economics, the semi-digital marketing practices applied emphasize business ethical values such as honesty, fairness, halal product guarantees, and the principle of benefit, so that it is in line with the principles of sharia-based business sustainability